Asas-Asas Perbezaan di Antara Aliran Sunni dan Syi'i - Daud, Zakaria @ Mahmod (Jurnal Usuluddin, 1995)
The controversial between the Sunnies and Shi'ies is a well known issue among the Malaysian society. Many people misunderstood the position of Shi'i according to Sunni. Therefore, this article attempts to explore the differences between Sunni and Shi'i in both its fundamental and secondary aspects.